The use of airspace: the organizational basis - Гусар, Ольга Анатоліївна; Куліш, Аліна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article defines the organization of airspace use in accordance with the norms of national and international legislation. The analysis of the current state of statistical indicators of the aviation industry associated with the use of airspace. For aviation remains an important question of the organization of airspace use, which depends Air Transport. However, be aware that the number and quality of air transport undertaken by aircraft depend on the balance between supply air traffic management of air traffic flow management and capacity at the optimum use of available resources and coordination on the part of aviation activity. During the flight the aircraft meant its movement in the air and hang. Moving aircraft carried out in the air and has a number of features: a) implementing air traffic in practice, it can not hold up on route for a long time and you can only stop landing aircraft; b) compared with other modes of transport aviation activity globally depends more on the understandings of international character and standards. Because of air traffic regulation requires organization and defining specific usage airspace. Organizational principles of the use of airspace defined public policy in aviation and largely depend on the development of the air transportation in Ukraine. An important strategic area is the improvement of the legal framework in terms of bringing it into line with modern international requirements generated by the EU and international organizations. Today topical issue for Ukraine in the field of aviation is the signing of the Common Aviation Area (SAP - a bilateral agreement between the EU and third countries) to establish common standards of safety and liberalization of market relations in the field of aviation. In fact, the CAP - a free trade area for aircraft that subsequently provide mutual access to markets of the aviation industry, air transport market, production and maintenance of aviation equipment, training aviation specialists and so on equal terms to all member states of the CAP. Given the international character of air traffic and decrease the number of flights served made aircraft and helicopters of foreign airlines, shows the need to improve service levels and increase safety in accordance with requirements of ICAO, Eurocontrol and the concept of CNS / ATM. Creating favorable conditions for attracting new airlines and introducing new technologies and international quality standards on the provision of air transport will increase the volume of passengers and cargo, including transit.